ENHANCING STUDENTS' UNDERSTANDING OF CONFLICT MANAGEMENT STYLES IN THE RAILWAY SECTOR - Prasetiyo, Alfian Yuda; Churniawan, Erifendi; Handoko, Handoko; Kurniawan, Safrudin (Madiun Spoor : Jurnal Pengabdian Masyarakat, 2025)
This community service activity, conducted in the form of technical training, aims to enhance students' understanding of various conflict management styles possessed by each individual. In this activity, participants are given the opportunity to identify the conflict management styles they use in dealing with different situations. Once participants understand their respective conflict management styles, the speakers provide an in-depth explanation of the advantages and disadvantages of each style. Additionally, participants are given insights into strategies that can be applied to effectively manage conflicts based on their conflict management styles. This activity was attended by 118 participants from the railway sector. Its implementation consists of three main stages. The first stage is a pre-test aimed at identifying participants’ initial understanding of conflict management styles. The second stage involves measuring each participant’s conflict management style using the Rahim Organizational Conflict Inventory II (ROCI-II), a valid and reliable instrument for categorizing individual conflict management styles. The third stage is the material delivery session, which focuses on a deeper understanding of the characteristics, advantages, and limitations of each conflict management style. Based on the measurement results, it was found that the majority of participants, specifically 97.5%, tend to use the collaborating conflict management style, which emphasizes cooperation and finding mutually beneficial solutions. Meanwhile, 2.5% of participants exhibit a tendency to use the avoiding conflict management style, characterized by efforts to evade conflicts in certain situations. These findings provide an overview of students’ preferences in handling conflicts and serve as a foundation for developing strategies to improve conflict management skills more effectively in the future.